Knockdown of NRSF Alleviates Ischemic Brain Injury and Microvasculature Defects in Diabetic MCAO Mice - He, Cheng-Feng; Xue, Wen-Jiao; Xu, Xiao-Die; Wang, Jian-Tao; Wang, Xin-Ru; Feng, Yi; Zhou, Hou-Guang; Guo, Jing-Chun (Frontiers in Neurology, 2022)
Diabetes is one of the major health problems in the world and worsens the outcome such as severer cognitive impairment in stroke patients with diabetes. However, the mechanisms underlying how diabetes contributes to worsened cognition and stroke outcome are not fully understood. Previous studies showed that diabetes triggers activation of the neuron restrictive silencer factor (NRSF), so does ischemic stroke. Here, we performed 30-min middle cerebral artery occlusion (MCAO) in diabetic mice, which were established by 8-week of high-fat-diet feeding and subsequently 5-day of streptozotocin injection (40 mg/kg body weight, i.p.). We found that diabetes enhanced the MCAO-induced elevation of NRSF and its corepressors HDAC1 and mSin3A in the hippocampus, whereas decreased β-TrCP level. By using histological/immunofluorescence staining and neurobehavioral testing, our results showed that the brain damage and learning/memory impairment was further aggravated in diabetic ischemic mice but significantly attenuated after stereotaxic injection of NRSF-shRNA. Meanwhile, by performing whole-brain clearing with PEGASOS, microvascular reconstruction, western blotting and ELISA, we found that NRSF-shRNA markedly alleviated the vasculature disorders and upregulated the decreased expression of NRP-1, VEGF and VEGFR2 in diabetic ischemic hippocampus. Therefore, our results demonstrated for the first time that the activation of hippocampal NRSF plays an important role in mediating the aggravated brain injury and cognitive disabilities in diabetic ischemic mice, which is possibly via the reduction of NRP-1/VEGF signaling.